Practical tips by peer support in chronic vestibular hypofunction: an exploratory survey - Vermorken, Bernd Lode; Schouten, Anna C.; van Laer, Lien; van Toor, Alonda; Devocht, Elke M. J.; van de Berg, Raymond (Frontiers in Neurology, 2024)
Introduction Patients with chronic vestibular hypofunction typically suffer from dizziness, imbalance and oscillopsia (blurred vision); symptoms that pose challenges to everyday life. Currently, advice on how to deal with such challenges is mainly provided by health care professionals (i.e., ENT-surgeons, neurologists, physiotherapists and psychologists). However, fellow patients with a similar condition and a true appreciation of the lived experiences, are likely to provide valuable support and advice as well. The purpose of this study, therefore, was to collect tips and advice from patients with chronic vestibular hypofunction. Methods An exploratory survey was designed to collect tips from fellow chronic vestibular hypofunction patients on how to cope with disease-related challenges in everyday life. The survey was distributed both online and in person. The list of tips was coded and analyzed thematically and deductively, by using the international classification of functioning, disability, and health (ICF) model. Results In total, 425 tips were obtained from the 179 participants. Most tips were coded under “environmental factors” (46%) and “activities and participation” (39%). The remaining tips were categorized as “body functions” (15%). No tips were about “body structures.” The participants coped with their daily struggles by investing in assistive products and technology, like adapted bikes, special footwear, walking frames. They described the importance of ensuring minimal light intensity for visibility (i.e., installing light sources in dark places). During activities, participants gave the advice to avoid bumpy roads and obstacles, and highlighted the necessity of adequate visual fixation to maintain balance. To ensure optimal activity, participants emphasized the importance of managing energy and taking sufficient rest. Discussion This study gives insight into how patients with chronic vestibular hypofunction cope with everyday struggles due to their symptoms. These tips can expand advice given by healthcare professionals. Knowing that fellow patients experience similar struggles and learned to deal with their struggles in adequate ways, might offer support and help patients focus on possibilities rather than on disabilities. Further research should investigate the effect of sharing tips to see whether improvement in (mental) health can be achieved in patients with chronic vestibular hypofunction.